Conversion to secondary progressive multiple sclerosis: Multistakeholder experiences and needs in Italy - Giovannetti, Ambra Mara (PLoS One, 2020)
BACKGROUND: Conversion to secondary progressive multiple sclerosis (SPMS) is associated with a relatively poor prognosis, and SPMS is responsible for the majority of the social and economic costs associated with MS. Managing the Transition to SPMS (ManTra) is a mixed methods project conducted in Italy and Germany aimed to set up a user-led resource to empower and improve the quality of life of newly diagnosed SPMS patients. AIMS: To assess the experiences and the needs of Italian people who recently converted to SPMS, patient significant others (SOs), neurologists and other health professionals (HPs). METHODS: We conducted 15 personal semistructured interviews (PSIs) with SPMS patients who transitioned up to five years, and three focus group meetings (FGMs), one of SPMS SOs, one of neurologists, and one of other HPs. Participants were purposely selected from the three geographic areas of Italy, and varied in terms of gender, education and (for patients) disease severity. PSIs and FGMs were audiorecorded, transcribed and analyzed by two researchers using the framework analysis. RESULTS: One hundred sub-categories were identified, grouped into 13 categories and four themes: ‘awareness of the transition’, ‘communication of the transition’, ‘dealing with symptoms worsening’, and ‘needs’. The major unmet needs were collected in four dimensions ‘organization and management; ‘empowerment training’; ‘information’; and ‘policies’. CONCLUSIONS: Two are the main findings: first, the widespread lack of awareness around the transition; second, the need to improve the quality of the care pathway in the Italian context. It was particularly stressed the need for a holistic and multidisciplinary approach (with patients and SOs as members of the team), the development of an ad hoc plan of follow up visits with easy access to MS specialists’ consultation/treatment; specialized training for each stakeholders; more information on SPMS, daily management and changes at policy level.